Analysis Of Monetary Variables and Zakat, Infaq and Sadaqah (ZIS) On Poverty In Aceh Province with Economic Growth as An Intervening Variable - Asnidar Asnidar; Nurlaila Hanum; Tengku Putri Lindung Bulan; Agustina Nurul Fajriah; Mayang Murni; Sri Rahayu Aprillia (Jurnal Ekuilnomi, 2026)
This study analyzes monetary variables and ZIS on poverty in Aceh Province through economic growth. The data used are secondary data sourced from Baitul Mal Aceh and the Central Statistics Agency, using path analysis. The results of the study indicate that inflation does not directly have a significant effect on economic growth in Aceh Province, while interest rates and ZIS have a direct significant effect on economic growth in Aceh Province. Inflation and economic growth do not directly have a significant effect on poverty in Aceh Province, while interest rates and ZIS have a significant effect on poverty in Aceh Province. However, inflation does not indirectly have a significant effect on poverty in Aceh Province through economic growth. Interest rates and ZIS have an indirect significant effect on poverty in Aceh Province through economic growth. These findings underscore the importance of evaluating ZIS management and distribution strategies by the government and related institutions, so that programs do not only focus on increasing economic growth, but also ensure that the benefits are felt directly by the poor. This study contributes to the literature on population economics by revealing the role of a combination of monetary policy and Islamic social financial instruments in poverty alleviation efforts in Aceh